ANALYSIS OF THEORETICAL APPROACHES TO ESTIMATION OF ECONOMIC VALUATION OF TRAVEL TIME VARIABILITY AND THE VALUE OF TRAVEL TIME SAVINGS OF URBAN PASSENGER TRANSPORT - V. Donchenko; R. Filippova (Вестник университета, 2018)
The overview of some theoretical approaches to the mechanism of economic valuation of travel time variability and the value of travel time savings of urban passenger transport is provided. Each estimate depends on the demographic characteristics of the population, the type of transport, time, location and purpose of the trip, as well as the available choice of alternatives. The decisions of experts in a context of consumption choice based on utility maximization, subject to constraints on income and the minimum amount of time required by each activity are described. There in sum, there is a broad consensus on the approach adopted and the relevant variables and categories, as well as a degree of similarity in the specific values recommended.